Pola Asuh Orang Tua Mempengaruhi Kemampuan Self Care Pada Anak Autisme - Ni Made Purnamaningsih; I Gusti Putu Satya Laksmi; Ni Luh Putu Devhy (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Autism is one of the serious development disorders of a child, which causes problem in the ability of daily life, one of which is self care. The role of parents, especially of parenting parents is very influential for self care ability in autistic children.Aims of this study is to analize corelation betwen parenting parents to self care ability in autism. Methods: The study design uses Descriptive Correlation, that is a correlation between two variables is parenting and ability self care in autistic children. With a Cross-Sectional approach. The amount of samples used was 47respondents, using the Purposive sampling technique and collecting data using The Pediatric Evaluation of Disability Inventory with the test results using the contingency coefficient. That tested whether there is a correlation between two variables is parenting and ability self care in autistic children. Results: The results of study found the majority of parents implementing democratic parenting as many as 25 people (53,2%) and 24 children (51,1%) with the ability to self care quite capable. The test results using the contingency coefficient obtained of p value of 0,000 (p<0,05) which means that these results indicate a correlation of parenting with ability self care in autistic children, a correlation strength value of 0,659 (strong power). Conclusion: The researcher suggests that parents provide many positive activities in terms of eating and drinking, dreesing, personal hygiene, and toileting so that children can independently do self care.